158k views
2 votes
(01.02 LC)Simplify negative 3 and 1 over 9 − negative 8 and 1 over 3.

negative 11 and 1 over 12
negative 5 and 2 over 9
5 and 2 over 9
11 and 1 over 12

User Moljac
by
5.5k points

2 Answers

0 votes

Answer:

C

Explanation:

5 and 2 over 9

User Frakod
by
5.3k points
4 votes

As we are given with


-3(1)/(9)-(-8(1)/(3))\\\\

we are supposed to simplify this expression. which can be done as below


\\=-3(1)/(9)+8(1)/(3)\\\\=(-28)/(9)+(25)/(3)\\\\=(-28+75)/(9)\\\\=-(47)/(9)\\


=5(2)/(9)

User Feofilakt
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.